A review of time reversal-based methods applied to fault location in power networks - Wang, Zhaoyang; He, Shaoyin; Razzaghi, Reza; Paolone, Mario; Xie, Yanzhao; Rachidi, Farhad (Frontiers in Energy Research, 2022)
Electromagnetic time reversal (EMTR)-based methods have been applied to the problem of fault location in power networks since 2012. Over the past decade, considerable theoretical investigations have led to a continuous improvement of the EMTR method in terms of fault location accuracy and efficiency. Meanwhile, different full-scale experiments, including pilot tests, were carried out, demonstrating the applicability and robustness of the EMTR method when applied to real power-system environments. This paper presents a review of the foregoing theoretical and experimental studies. Furthermore, suggestions for future studies are propounded, along with discussing various challenging research questions that still need to be addressed.